2022
DOI: 10.1038/s41598-022-15828-w
|View full text |Cite
|
Sign up to set email alerts
|

Research on water seepage detection technology of tunnel asphalt pavement based on deep learning and digital image processing

Abstract: To improve the safety of road tunnel pavement, the research established road tunnel pavement water seepage recognition models based on deep learning technology, and a water seepage area extraction model based on image processing technology to finally achieve accurate detection of water seepage on tunnel pavements. First, the deep learning models EfficientNet water seepage recognition model and MobileNet water seepage recognition model were built, the models were trained with the self-collected pavement seepage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In the classification task, Wu et al adopted DenseNet and deconvolution network framework for pixel-level detection and combined it with a support vector machine classifier to classify cracks, achieving 98% accuracy [31]. Li et al constructed EfficientNet and MobileNet models, respectively, to identify pavement water seepage problems, and the research results showed that EfficientNet performed well and could accurately detect pavement water seepage [32]. Martinez-Ríos et al used generalized Morse wavelet (GMWs) to perform continuous wavelet transform on vehicle vertical acceleration data for the detection of transverse cracks in the road surface and fine-tuned GoogLeNet, SqueezeNet, and ResNet18 [33].…”
Section: Model Selectionmentioning
confidence: 99%
“…In the classification task, Wu et al adopted DenseNet and deconvolution network framework for pixel-level detection and combined it with a support vector machine classifier to classify cracks, achieving 98% accuracy [31]. Li et al constructed EfficientNet and MobileNet models, respectively, to identify pavement water seepage problems, and the research results showed that EfficientNet performed well and could accurately detect pavement water seepage [32]. Martinez-Ríos et al used generalized Morse wavelet (GMWs) to perform continuous wavelet transform on vehicle vertical acceleration data for the detection of transverse cracks in the road surface and fine-tuned GoogLeNet, SqueezeNet, and ResNet18 [33].…”
Section: Model Selectionmentioning
confidence: 99%